Alat Dan Media Pembelajaran Dalam Perspektif Tafsir Al-Misbah - Gunawan Gunawan; Selamat Pasaribu (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2022)
Learning tools and media in Islamic education perspective). Every human being always undergoes a learning process throughout his life. The learning process is caused by the interaction between humans and their environment. For this reason, learning occurs whenever and wherever. "Learning is characterized by a change in a person's behavior caused by changes in the level of knowledge, skills, or attitudes. Media has a very important role in the teaching and learning process. In the use of media sometimes there are pros and cons that result in some Muslims not wanting it (the group considers the media and tools not in Islam) and some others embrace it. The existence of this research will be a bright spot for the study and understanding of Muslims in the use of media and learning tools. The study method in this study uses literature studies related to the arguments of the Qur'an and the interpretations of leading interpreters such as Alimisbah, Almaraghi, Tafsir Al-Azhar, Tafsir Al Zhilalil Qur'an and Tafsir al-Maraghi. In this literature research it was found that in the Qur'an contained in Surah An Nahl: 44 and 125, Al Muzammil: 20, At Taubah: 11, Al Baqarah: 31, An Naml: 29, 30 and 44, Al Ahzab: 21 and Al Maidah: 2, this whole verse represents the whole argument for the use of learning tools and media in education, so it is clear that the Universe has a lot of media diversity, both in the form of cases in social society, the history of the previous prophets to the rewards and rewards. for those who do, all of it is contained in the Qur'an Al Karim.